Traumatic posterior communicating artery-cavernous fistula, angioarchitecture, and possible pathogenesis: a case report and literature review - Du B; Zhang M; Liu Q; Shen J; Wang Y (Neuropsychiatric Disease and Treatment, 2016)
Bin Du,1,* Meng Zhang,2,* Qing-Lin Liu,2 Jie Shen,2 Yun-Yan Wang21Department of Neurosurgery, Jinan Central Hospital Affiliated to Shandong University, 2Department of Neurosurgery, Qi Lu Hospital, Shandong University, Jinan, People’s Republic of China*These authors contributed equally to this workAbstract: Carotid-cavernous fistulas (CCFs) are an abnormal vascular shunt between the carotid artery and the cavernous sinus, and were traditionally classified into four subtypes based on the detailed fistulas anatomy and arterial supply. CCFs are frequently encountered in patients with traumatic skull base fractures. In this report, we present one such case caused by two head traumas. Computed tomography and digital subtraction angiography confirmed that this CCF arose from posterior communicating artery of the internal carotid artery, which is not included in the traditional Barrow et al’s categorization. The possible mechanisms include laceration of dural mater of posterior clinoid process and laceration or pseudoaneurysm formation of posterior communicating artery. This case was successfully treated with endovascular coil embolization.Keywords: carotid-cavernous fistulas, cavernous sinus, CCF, PComA, posterior communicating artery